Formulation and Stability Evaluation of Carrot Extract (Daucus carota L.) Scrub Lotion as a Natural Moisturizer - Mahardika, Muladi Putra; Okta Riyan, Putri; Vera Vero Nika, Melinda (Journal Syifa Sciences and Clinical Research, 2025)
Carrots contain bioactive compounds such as beta-carotene and vitamin E that protect the skin against oxidative stress, maintain hydration, and delay premature aging. This study aimed to formulate and evaluate scrub lotions containing Daucus carota L. extract at concentrations of 2%, 4%, and 6%. The formulations were tested for physicochemical stability (organoleptic properties, pH, homogeneity, adhesion, and spreadability), moisturizing effect, and consumer acceptability. All formulations were stable, homogeneous, and within the safe pH range. The 6% formulation (Formula III) showed the most pronounced effect, significantly increasing skin hydration to 35% after 12 days of application (p 0.05). These findings demonstrate the potential of Daucus carota L. extract as a natural, safe, and effective active ingredient for moisturizing and anti-aging cosmetic products. To the best of our knowledge, this is among the first studies to systematically evaluate the stability and moisturizing efficacy of carrot extract scrub lotion, although further clinical investigations are required to confirm long-term safety and performance.